Entre o real e o abstrato : materialização do projeto ético-político profissional do assistente social - Bairro, Emilene Oliveira de (2016)
This dissertation deals about the materialization of the Professional Project Ethical-Political (PEPP) of the social workers, and searches for an answer to the following research problem: How does the PEPP is materialized on the daily social workers’ interventions? This dissertation aims to analyze the way in which social workers materialize the Professional Project in order to contribute for the debate of the professional category and stimulate a reflective professional practice. To this end, we recreate the historical process of the profession in Brazil, since its genesis until the theoretical-methodological maturation, which is based on the Marx's Critical Social Theory. This recreation allowed us to understand the formation and setting of PEPP, based on the Laws of the Profession Regulamentation, the Professional Ethical Code, and on the ABEPSS’s guidelines. The Dialectical-Critical method is present in every part of the creation of this work, along with the contribution of categories such as totality, historicity, and contradiction to the obtention and analysis of the phenomena in the concrete reality. To achieve the study goals, we made a qualitative research collecting empirical data and making a bibliographical and documental analysis on the course of Specialization in Social Intervention with Families from the Faculty of Social Work of PUCRS, since we understand that this is a place with the permanent promotion of education. In the evaluation of the social workers’ answers to the questions of the instrument, we notice, through content analysis, that there are possibilities for the PEPP materialization once the professional actions agree with the social and political direction of the profession, which has as main goals the human emancipation and the social transformation. We highlight that PEPP is a theme that needs more discussion in the knowledge production of the Brazilian Social Work due to its importance to the understanding of the profession as well as the real possibilities that it allows the professional to achieve by materializing the project within the limits imposed by the capitalist society.